Content validity of the short version of the subscale of the State-Trait Anxiety Inventory (STAI) (Revista Latino-Americana de Enfermagem, 2011)
The goal was to describe the content validity of a short version of the state subscale of Spielberger's "State-Trait Anxiety Inventory (STAI)", based on the original version adapted to Spanish, in Spanish patients receiving invasive mechanical ventilation (IMV). The sample consisted of 16 patients receiving IMV at the Alicante Hospital (Spain), who selected the items from the full Spanish version of the STAI-state that were most relevant to them. Items 1, 5, 9, 10, 12 and 20 from the original scale are the most relevant for the Spanish patients receiving IMV and 5 of these are included in the short version of the scale (83.3% agreement). The short scale has shown adequate content validity for Spanish patients receiving IMV.